WAYS TO INCREASE RAILWAY COMPETITIVENESS (Transport systems and technologies, 2023)
Nowadays, railway transport is the most developed in Ukraine. It is the heart of transport services for individuals and legal entities, without it is difficult to imagine the normal functioning of production facilities and logistics firms. Rail transport also occupies the main place among domestic traffic. Passenger transportation occupies a significant place in the work of transport, so suburban transportation occupies the second place in terms of mass transportation after intercity transportation by automobile transport . The demand for this type of transportation can be called elastic, since there is an impact of seasonality on transportation, for example, the beginning and ending of academic semesters, vacation time. Therefore, it is advisable to consider tourist trains that could run on sections of the Dnіpro-Pіvdennij station – Apostolovo station, Dnіpro-Pіvdennij station – Surskoye station, Dnіpro-Pіvdennij station – Zhovtokamenka station, Dnіpro-Pіvdennij station – Elizarovo station. The article provides graphs of the movement of these trains, allowing passengers to visit attractions along the entire route. Consequently, tourist routes can improve the development of tourism throughout Ukraine, and not popular destinations. This may result in increased demand for tourist trains, increased monetization of passenger transportation, thereby improving passenger comfort.
Keywords: railway transport, passenger transportation, tourist trains, tourist routes.